On Kant's Conception of Inner Sense: Self‐Affection by the Understanding. (8th May 2013) - Schmitz, Friederike
Abstract: Among the extensive literature on the first Critique, very few commentators offer a thorough analysis of Kant's conception of inner sense. This is quite surprising since the notion is central to Kant's theoretical philosophy, and it is very difficult to provide a consistent interpretation of this notion. In this paper, I first summarize Kant's claims about inner sense in the Transcendental Aesthetic and show why existing interpretations have been unable to dissolve the tensions arising from the conjunction of these claims. Secondly, I present my own reconstruction of Kant's model of inner sense, relying essentially on Kantian considerations found in the B‐version of the Transcendental Deduction. My main idea is that inner sense, for Kant, is a passive faculty that gets affected by the understanding performing its figurative synthesis on material given in outer sense. In the remainder of the paper, I highlight a few consequences of my interpretation and outline ways to deal with some objections.